Development of a hub and spoke model for quality improvement in rural and urban healthcare settings in India: a pilot study - Manish Jain; Vikram Datta; Ankur Sooden; Mahtab Singh; Sushil Srivastava; Rahul Garde; Harish Pemde; Poonam Shivkumar; Akash Bang; Prabha Kumari; Sonia Makhija; Tarun Ravi; et al. (BMJ Open Quality, 2020)
Objective Hub and spoke model has been used across industries to augment peripheral services by centralising key resources. This exercise evaluated the feasibility of whether such a model can be developed and implemented for quality improvement across rural and urban settings in India with support from a network for quality improvement.Methods This model was implemented using support from the state and district administration. Medical colleges were designated as hubs and the secondary and primary care facilities as spokes. Training in quality improvement (QI) was done using WHO’s point of care quality improvement methodology. Identified personnel from hubs were also trained as mentors. Both network mentors (from QI network) and hub-mentors (from medical colleges) undertook mentoring visits to their allotted facilities. Each of the participating facility completed their QI projects with support from mentors.Results Two QI training workshops and two experience sharing sessions were conducted for implementing the model. A total of 34 mentoring visits were undertaken by network mentors instead of planned 14 visits and rural hub-mentors could undertake only four visits against planned 18 visits. Ten QI projects were successfully completed by teams, 80% of these projects started during the initial intensive phase of mentoring. The projects ranged from 3 to 10 months with median duration being 5 months.Discussion Various components of a health system must work in synergy to sustain improvements in quality of care. Quality networks and collaboratives can play a significant role in creating this synergy. Active participation of district and state administration is a critical factor to produce a culture of quality in the health system.